Nanostructured Cobalt Tungstate (CoWO4): A Highly Promising Material for Fabrication of Protective Oxide Film on Copper in Chloride Medium. Issue 16 (17th December 2019) - Chukwuike, V. I.; Sankar, S. Sam; Kundu, Subrata; Barik, R. C.
Abstract : Cobalt tungstate (CoWO4 ) oxide film having average thickness ∼204 nm was formed on a copper surface through a simple wet-chemical method in 3.5% NaCl solution containing the dispersed oxide. This film was found to stabilize the unstable copper oxide film and screen off the substrate from contact with the corrosive electrolyte. In the present study, a nonionic surfactant, Triton X-100, was employed for the synthesis of CoWO4 nanoparticles to improve its aqueous dispersibility and adherence to the copper surface. After the dispersion of CoWO4, a barrier layer was formed which acted to provide excellent corrosion resistance for the copper metal in the corrosive medium. Electrochemical studies revealed superior corrosion protection of the selected combination, CoWO4 + Triton X-100 compared to their separate use. A reduction in corrosion current density from 7.84 to 0.78 μA cm −2  with a 90% average inhibition efficiency was observed. Post corrosion analysis of the film with respect to changes in morphology, composition, film thickness and microstructure was carried out using advanced characterization techniques to verify the robustness of the material. All the analyses indicate a good coverage of Cu surface by the prepared inhibitor.